Refurbishment and conversion of the Museum of Sacred Art in Évora. Portugal - Sequeira, Marta (TC Cuadernos, 2022)
The Museum of Sacred Art project consisted of the remodelling and conversion of the former Colégio dos Moços do Coro – a three-storey building of Baroque architecture. The complex, originally built in the late 17th century, was badly damaged by its subsequent use – the result of successive installations of different school facilities. After reading the text "Exposição de Serralves 5", by Álvaro Siza – in which he reflected on the Picasso Museum in Antibes, installed in a castle where there was not, after all, a single sign of its musealization – Carrilho da Graça tried to do a kind of restoration, fixing the architecture of the dominant historical period. Intrusive walls were demolished, as well as vaults and partition walls between cells were rebuilt. The adaptation of the building to the new programme was carried out, however, without the signs typical of the installation of a museum, since the light is irradiated from displays and mouldings, the ventilation is natural and the air conditioning is done through underfloor heating and from the outside of the vaults – avoiding the proliferation of gutters, spotlights and grids. Lighting, ventilation and air conditioning were thus introduced without distorting the perception of the space.